Application of Neural Networks in The Process of Biometric Authentication - Zbigniew PIOTROWSKI; Mateusz MIKULSKI (Communications of International Proceedings, 2021)
The purpose of this paper is to present the selected biometric security measures based on artificial intelligence that ensure user authentication. Biometrics as a method of automatic recognition of people based on their physical characteristics can be used in the process of authentication or authorization of users using data, devices, systems and programs. In this paper, biometric techniques will be described, followed by an example of the use of the iris user verification method, along with an indication of the open-source resources that enable creation.
Keywords: Biometrics; Convolutional Neural Networks; Security; Authentication.